Refugee women in Britain and France - Allwood, Gill; Wadia, Khursheed (Book collections on Project MUSE., 2013)
'This book is about the lives of refugee women in Britain and France. Who are they? Where do they come from? What happens to them when they arrive, while they wait for a decision on their claim for asylum, and after the decision, whether positive or negative?It shows how laws and processes designed to meet the needs of men fleeing political persecution often fail to protect women from persecution in their home countries and fail to meet their needs during and after the decision-making process. It portrays refugee women as resilient, resourceful and potentially active participants in British and French social, political and cultural life. It exposes the obstacles that make active participation difficult. The book is an authoritative and thorough synthesis of all available material on refugee women in Britain and France. The style is accessible and highly readable, making this an ideal book for academics, students and interested readers' --Back cover.